2015
DOI: 10.5935/1415-2762.20150070
|View full text |Cite
|
Sign up to set email alerts
|

Drug interaction in elderly inpatients in the emergency department of a university hospital

Abstract: Objetivo: identificar a ocorrência de potenciais interações medicamentosas em prescrições médicas de idosos internados no Serviço de Emergência. Métodos: estudo transversal, amostra composta de 101 prescrições médicas das primeiras 24 horas de internação de idosos na sala de Emergências Clínicas do Pronto-Socorro. A análise das interações medicamentosas foi realizada pela base de dados Drugs.com, classificadas quanto ao potencial de interação em: grave, moderada e leve. Resultados: o número de medicamentos das… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…However, it requires attention to the adequate planning of the drugs and their intervals, preventing possible drugs interactions and damages to patients. 23 It is worth highlighting that in the study 100 different types of drug-drug interactions were found, of which 61 types of drugs interactions that showed greatest frequency in the two institutions studied. One of the serious more prevalent drugs interactions was the association of the drugs amlodipine and simvastatin, observed in 5 (3.7%) medical prescriptions.…”
Section: Discussionmentioning
confidence: 94%
“…However, it requires attention to the adequate planning of the drugs and their intervals, preventing possible drugs interactions and damages to patients. 23 It is worth highlighting that in the study 100 different types of drug-drug interactions were found, of which 61 types of drugs interactions that showed greatest frequency in the two institutions studied. One of the serious more prevalent drugs interactions was the association of the drugs amlodipine and simvastatin, observed in 5 (3.7%) medical prescriptions.…”
Section: Discussionmentioning
confidence: 94%
“…Como exemplo, o uso de difenidramina pode auxiliar na identificação de reação adversa a medicamentos, quando se observa rush cutâneo, prurido e outras reações locais (33) . A administração de heparina (incluindo enoxaparina, fondaparinux, bivalrudin), isoladamente ou combinada com outros medicamentos de uso habitual, remete a complicações de ordem hemorrágica (36) . Sendo assim, seu uso, como bem como o de vitamina K, que é antagonista dos anticoagulantes, são indicativos de EA relacionados à distúrbios hemorrágicos.…”
Section: Acetilcisteínaunclassified
“…29 It is important to emphasize in the scope of the DIs that nurses must pay attention to the period of the medical prescriptions in order to avoid that drugs that may interact and/or interfere with the effectiveness of the treatment are administered simultaneously, ensuring the proper drug administration and their intervals, redu-cing the potential adverse events associated with DIs. 30…”
Section: Drug Interactions In One Intensive Care Unitmentioning
confidence: 99%